The relationship between macroeconomic factors towards housing prices in Malaysia / Nurul Ain Yaakob - Yaakob, Nurul Ain (Faculty of Business and Management, 2015)
This main purpose of this study is to examine the relationship between macroeconomic variables towards housing price in Malaysia. This paper examines empirically whether the increasing trend in the Malaysian housing price is related to changes in Gross Domestic Product (GDP), inflation rate and unemployment rate. Over the past few years, the house price of Malaysia has experienced significant price expansion. The study explores the relationship between the house price and the independent variables for 15 years starting Q1 2000 to Q3 2014 using 60 secondary data of each variables. In the process of findings there are few types of analysis were tested using Eviews Version 7.0, such as simple linear regression analysis. The result indicates that there are significantly related to house price. The paper is useful for investors, speculators, policies makers and buyers to know which factors to account for in housing investment decision. This paper can also serve as a guide for the government in stabilizing the residential housing price in Malaysia.